2002
DOI: 10.4049/jimmunol.168.11.5596
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Light Chain Allelic Exclusion and Lack of Positive Selection in Immature B Cells Expressing Incompetent Receptor Deficient of CD19

Abstract: Positive signaling is now thought to be important for B cell maturation, although the nature of such signals has not yet been defined. We are studying the regulatory role of B cell Ag receptor (BCR) signaling in mediating positive selection of immature B cells. To do so, we use Ig transgenic mice (3-83Tg) that are deficient in CD19, thus generating a monoclonal immature B cell population expressing signaling-incompetent BCR. Immature 3-83Tg CD19−/− B cells undergo developmental arrest in the bone marrow, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 71 publications
6
81
0
Order By: Relevance
“…Moreover, autoreactivity may not be the only way to promote receptor editing because some non-autoreactive knockin mice also showed extensive secondary rearrangements, likely due to a low expression of the knockin gene (27,28). It was also shown in CD19-deficient mice that a low BCR signaling could impair LC allelic exclusion (29). This finding is reminiscent of observations that HC and LC transgenes only induced allelic exclusion when expressed above a certain threshold (30).…”
supporting
confidence: 56%
“…Moreover, autoreactivity may not be the only way to promote receptor editing because some non-autoreactive knockin mice also showed extensive secondary rearrangements, likely due to a low expression of the knockin gene (27,28). It was also shown in CD19-deficient mice that a low BCR signaling could impair LC allelic exclusion (29). This finding is reminiscent of observations that HC and LC transgenes only induced allelic exclusion when expressed above a certain threshold (30).…”
supporting
confidence: 56%
“…This effect was negated in homozygous knock-in mice expressing higher levels of surface IgM. Additionally, incomplete isotype exclusion has been documented in mutant mice lacking the tyrosine kinase Lyn [26] or CD19 [27]. The finding that negative selection of immature B cells was intact in the absence of Syk was unexpected due to the loss of BCR-mediated signaling events in syk -/-transformed avian lymphocytes [11].…”
Section: Resultsmentioning
confidence: 99%
“…RNA and cDNA Analysis-RNA preparation and RT-PCR amplification for RAG-2, B220, and actin were performed as we have described previously (23,26). PCR conditions and primer sequences were as described previously (23,26).…”
Section: Methodsmentioning
confidence: 99%
“…While most of the published data has probed the role of these co-receptors only upon BCR ligation, little is known about their function in regulating the ligand-independent BCR tonic signals in unstimulated cells. In an earlier study we showed that immature 3-83Tg CD19 Ϫ/Ϫ B cells fail positive selection and undergo intensive receptor editing in an attempt to express a new receptor (23). These studies raised the hypothesis that CD19 expression is important to set BCR tonic signaling for positive selection and provided a possible link between failure of positive selection and activation of receptor editing in immature B cells.…”
mentioning
confidence: 99%